1974
DOI: 10.1172/jci107533
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Properties of Human and Canine Plasmins

Abstract: Three kinds of plasmin were found to be generated when plasminogen or [UI]plasminogen was incubated at 320C for longer than 20 min in urokinase and 50% glycerol. Each plasmin was then separated by G-200 or G-75 Sephadex filtration, and its physicochemical properties were determined. The molecular weights of the three 'plasmins as determined by G-200 Sephadex filtration were 125,000±5,000( SD), 63,000+2,000 (SD), and 31,500+1,000(SD), and those by sodium dodecyl sulfate ( SDS) -polyacrylamide electrophoresis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The molecular weight of plasmin monomer is approximately 32,000 (27) and is much smaller than those of FDP and albumin. Only the monomer type of plasmin is detected in vivo (Y. Takeda, personal communication).…”
Section: Discussionmentioning
confidence: 92%
“…The molecular weight of plasmin monomer is approximately 32,000 (27) and is much smaller than those of FDP and albumin. Only the monomer type of plasmin is detected in vivo (Y. Takeda, personal communication).…”
Section: Discussionmentioning
confidence: 92%
“…To examine the possibility that an abnormality in neuraminic acid might be responsible for the apparent increase in molecular weight of the nonfunctional inhibitors, the inhibitor preparations were incubated with varying concentrations of neuraminidase for I It is not clear why the glycerol-activated plasmin-Ci inactivator complex failed to remain intact in the presence of SDS and urea. One possibility is suggested by the study of Takeda and Nakabayashi, which demonstrated that glycerolactivated plasmin underwent autodigestion and therefore possessed a lower molecular weight than did freshly activated plasmin (13). These considerations have suggested that the degraded enzyme may have a deficiency in binding sites and hence may form a complex with C!…”
Section: Resultsmentioning
confidence: 99%
“…It is our feeling that the fibrinogen molecule, whether *I-labelled or not is quite delicate. This may be partly due to its propensity to accompany plasminogen or adsorb to plasmin [259] during purification. Thus we take great care with our preparations for metabolic experiments.…”
Section: Satisfactory Labelling Of Fibrinogen With Radioactive Iodinementioning
confidence: 99%